2012
DOI: 10.1016/j.neuron.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Neocortical Dynamics Predict Behavioral Categorization of Sounds

Abstract: The ability to group stimuli into perceptual categories is essential for efficient interaction with the environment. Discrete dynamics that emerge in brain networks are believed to be the neuronal correlate of category formation. Observations of such dynamics have recently been made; however, it is still unresolved if they actually match perceptual categories. Using in vivo two-photon calcium imaging in the auditory cortex of mice, we show that local network activity evoked by sounds is constrained to few resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
235
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(273 citation statements)
references
References 47 publications
33
235
0
5
Order By: Relevance
“…Their activation is accompanied by elevated firing in the corresponding neural ensemble and population oscillations in the gamma range. Our stimulus induced change of state is thus congruent with discrete firing rate changes (Bathellier et al, 2012) and stimulus induced alpha to gamma transitions observed in vivo. We interpret the activation of a stimulated coding attractor as successful stimulus detection and study how the phase, power, and synchronization of ongoing alpha oscillations modulate performance.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Their activation is accompanied by elevated firing in the corresponding neural ensemble and population oscillations in the gamma range. Our stimulus induced change of state is thus congruent with discrete firing rate changes (Bathellier et al, 2012) and stimulus induced alpha to gamma transitions observed in vivo. We interpret the activation of a stimulated coding attractor as successful stimulus detection and study how the phase, power, and synchronization of ongoing alpha oscillations modulate performance.…”
Section: Introductionsupporting
confidence: 83%
“…1A). These minicolumns do not necessarily correspond to anatomical columns but rather to local subgroups of cells that tend to be connected (Yoshimura et al, 2005;Kampa et al, 2006) and coactive (Bathellier et al, 2012). Each layer 2/3 portion of a minicolumn contained 30 pyramidal cells (Peters and Yilmaz, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, various Ca 2+ indicators including rhod-2 [6], fura-2 [7,8], OGB-1 [9][10][11][12][13], fluo-2 [14], fluo-4 [9,15,16], Alexa Fluor 594 together with fluo-5F [17,18], and genetically encoded Ca 2+ indicators (GCaMP3 [1] and GCaMP6s [3]) [14,19,20] have been widely used in studies of the Au1 with two-photon Ca 2+ imaging in both in vitro and in vivo conditions. The in vivo experiments, particularly the functional mapping experiments, have provided important insights into the topographic organization of the Au1, but the degree of precision in tonotopic mapping has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…We tested whether coupling was due to global population changes 28,29 or to coordinated activity in small neuronal groups 30 by comparing the performance of variants of the coupled model. We compared coupled models that included as coupling predictors only the mean population activity or the activity of factorized subsets of cells.…”
mentioning
confidence: 99%